2019
DOI: 10.1007/s00027-019-0629-0
|View full text |Cite
|
Sign up to set email alerts
|

If Alpine streams run dry: the drought memory of benthic communities

Abstract: Several mountain streams are currently changing from perennial to temporary due to increasing water abstraction and global climate change with expected detrimental effects on stream biodiversity and functionality. We here examined whether macroinvertebrates and diatoms, experiencing recurring non-flow periods, show alterations even after complete flow resumption in 13 mountain streams in SW Italian Alps. Benthic communities were sampled after complete flow resumption in April 2017 in a control section, with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 87 publications
8
52
3
Order By: Relevance
“…When considering the effect of flow intermittency on the three examined genera, our results showed that abundances of the three genera were lower in intermittent than in permanent reaches, in agreement with our second hypothesis. This is in accordance with the results observed in a related study performed in the same study area, where we observed a significant negative effect of flow intermittency on the relative abundance of scrapers taxa (Piano et al, 2019a). This reduction is due to the lower availability of organic matter in intermittent than in permanent sites, which is in turn potentially determined by the lower retention capacity of the riverbed substrate in intermittent sites.…”
Section: Effects Of Flow Intermittency On the Ecological Niches Of Nesupporting
confidence: 93%
See 3 more Smart Citations
“…When considering the effect of flow intermittency on the three examined genera, our results showed that abundances of the three genera were lower in intermittent than in permanent reaches, in agreement with our second hypothesis. This is in accordance with the results observed in a related study performed in the same study area, where we observed a significant negative effect of flow intermittency on the relative abundance of scrapers taxa (Piano et al, 2019a). This reduction is due to the lower availability of organic matter in intermittent than in permanent sites, which is in turn potentially determined by the lower retention capacity of the riverbed substrate in intermittent sites.…”
Section: Effects Of Flow Intermittency On the Ecological Niches Of Nesupporting
confidence: 93%
“…These newly temporary streams are characterized with recurrent non-flow events, occurring in summer, followed by rewetting phases in late autumn (Fenoglio et al, 2010) due to the interactive effects of both climate change and anthropogenic disturbance (Belmar et al, 2019;Bruno et al, 2019). These recurrent drying events are expected to alter the distribution of lotic biota by influencing physical conditions and distribution of trophic resources (e.g., Calapez et al, 2014;Elias et al, 2015;Milner et al, 2017;Doretto et al, 2018;Falasco et al, 2018;Piano et al, 2019a;Doretto et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow cessation results in the loss of the longitudinal connectivity and isolation of stream reaches with consequences on population survival, the diversity of aquatic communities, and transport and storage of organic matter subsidies (Datry et al 2016b;Doretto et al 2020). Such adverse conditions may be exacerbated by the effect of anthropogenic-induced hydromorphological alterations at the local scale, such as damming and water abstraction (Grubbs and Taylor 2004;Holt et al 2015;Doretto et al 2019;Piano et al 2019). Regardless of the nature of these alterations (i.e., natural or human-induced), RCC poorly adapts to lotic ecosystems experiencing changes in flow regime, with deviations from its predictions probably depending on the components of the flow regime that are mostly modified (i.e., magnitude, frequency, duration, timing, and flashiness).…”
Section: The Role Of Natural Discontinuitiesmentioning
confidence: 99%